The Price Entitlement Effect: When and Why High Price Entitles Consumers to Purchase Socially Costly Products - Lee, Saerom; Winterich, Karen Page (Journal of Marketing Research, 2022)
This research investigates when and why consumers purchase products with social costs (e.g., environmental harm). Six studies demonstrate that upper-class consumers are more likely to purchase a product with social costs when it has a higher price because they experience greater entitlement, which the authors term the “price entitlement effect,” allowing for purchase justification. In contrast, lower-class consumers do not feel entitled to purchase a product with social costs when it is higher-priced. This effect occurs because upper-class consumers tend to have a greater self-focus, with a higher price entitling them to more resources than others. Consistent with the entitlement mechanism, when egalitarian values are made salient, the price entitlement effect is mitigated, reducing upper-class consumers’ purchase of socially costly products. Notably, the price entitlement effect occurs only when products have social costs rather than for all higher-priced products. However, when the social costs of a product are severe, price entitlement does not sufficiently justify product purchase. This research provides theoretical and practical insights regarding when and why higher price entitles purchase of socially costly products, contributing to research on social class and socially responsible (vs. costly) consumption as well as choice justification.